Measuring how armed conflict impacts economic growth in sub-Saharan Africa through spatial analysis - Ogbe, Michael Abimbola; Abdullahi, Malanta Sabiu; Ding, Yibing (Frontiers in Political Science, 2024)
This study investigates the spatial effects of armed conflict on Sub-Saharan Africa’s (SSA) economic growth, focusing on Central Africa, East Africa, and West Africa. Utilizing Spatial Durblin Model (SDM), the analysis reveals significant spatial effects of armed conflict intensity, indicating that conflict in neighboring countries influences conflict levels within a focal country. The study finds a weak or inconclusive relationship between GDP per capita (GDPpc) and conflict intensity, with East Africa showing a significant negative association, suggesting that higher economic prosperity in neighboring countries may mitigate conflict. Conversely, higher corruption levels in Central and West Africa are positively associated with increased conflict intensity, highlighting corruption’s destabilizing influence. Spatial lag SDM results suggest potential benefits of regional economic cooperation in reducing conflict intensity. Moreover, significant positive spatial autocorrelation underscores the interconnected nature of conflict within SSA, with West Africa exhibiting more pronounced spatial spillover effect. Findings from Spatial Autoregressive (SAR) models confirm the weak association between GDPpc and conflict intensity but emphasize the consistent positive association between corruption and conflict intensity. Additionally, the Spatial Error Model (SEM) reaffirms corruption’s detrimental impact on governance and stability. Additionally, the hypothesis of a significant difference in the effect of armed conflict across different SSA subregions is supported, with Central Africa experiencing the strongest negative impact on economic growth, followed by East and West Africa. The study highlights substantial regional heterogeneity in the economic consequences of armed conflict, emphasizing the need for regionally tailored policy interventions to address conflict-related economic disruptions in SSA.